The Aprende en casa program, a strategy that exludes minority language users? - Cruz-Aldrete, Miroslava (2021)
In this paper I discuss the complex situation faced by minority linguistic groups, in particular deaf users of the Mexican Sign Language (LSM), whose bilingual education was threatened by the educational crisis caused by the pandemic. The response of the Mexican state not to interrupt the education of children and young people in this country, made clear the discrimination against users of languages distinct of Spanish, as this is the vehicular language for the programming “Aprende en casa”, and doesn’t considerer the context and languages if the indigenous and deaf communities for their teaching.